2010
DOI: 10.1002/ange.201003485
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Graphene‐Encapsulated Oxide Nanoparticles: Towards High‐Performance Anode Materials for Lithium Storage

Abstract: Electrochemically active metals and metal oxides such as Sn, [1] Si, [2] SnO 2 , [3] and Co 3 O 4 [4] have long been considered as anode materials for lithium ion batteries because of their high theoretical capacities. However, a large specific volume change commonly occurs in the host matrix of these metals and metal oxides during the cycling processes, thus leading to pulverization of the electrodes and rapid capacity decay. [1][2][3] To circumvent these obstacles, carbonaceous materials with high electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
226
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(232 citation statements)
references
References 35 publications
3
226
1
2
Order By: Relevance
“…GO is an active material, it can act as surfactant [8], covalently combined with other materials [9], etc. In recent years, graphene hybrid nano particles appeared [10][11][12], the active GO sheets can be used to modify conventional nanoparticles which were used in polymer nanocomposites. PVDF is a polar polymer with excellent chemical, mechanical and electrical properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…GO is an active material, it can act as surfactant [8], covalently combined with other materials [9], etc. In recent years, graphene hybrid nano particles appeared [10][11][12], the active GO sheets can be used to modify conventional nanoparticles which were used in polymer nanocomposites. PVDF is a polar polymer with excellent chemical, mechanical and electrical properties [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Another major issue with LIBs at present are the chemical stability of the active material and decrease in cyclic performance. Recent research has suggested the incorporation of conductive materials such as CNT's and carbon particles to increase specific capacity [138][139][140][141]. Yoo et al [136] have reported the use of GNS in rechargeable LIB and it was also reported the increase in specific capacity of the electrode through the interaction of GNS with C60 and CNT.…”
Section: Energy Storagementioning
confidence: 99%
“…Graphene-encapsulated -CO3O4 was used as an anode material to improve the performance of LIB. It was reported that the energy density of 1100 mAh/g and current density of 74 mA/g [138]. Wu et al [139] have reported that the synthesis of graphene-anchored CO3O4 as the anode material in LIBs to improve the capacity and cyclic performance and the values were noted as 935 mAh/g of energy density and 50 mA/g of current density at 30 cycles.…”
Section: Energy Storagementioning
confidence: 99%
“…For instance, the novel 2D nanostructure has been intensively implemented to explore potential applications on super-capacitor, batteries, field-effect transistors (FETs), optical sensors and so on [12,13].…”
Section: Introductionmentioning
confidence: 99%